ANALISIS KESALAHAN BERBAHASA INDONESIA MAHASISWA PROGRAM STUDI PENDIDIKAN TATA RIAS ANGKATAN 23 UNIVERSITAS NEGERI MEDAN - Gaol, Yohana Putri Lumban; Tarigan, Inez Diameda Br; Lentina Pardede; Challista, Ega Marsha ⁠; Ananda, Aurum Suci; Daulay, Muhammad Anggie Januarsyah (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to analyze the use of Indonesian language by students of the Cosmetology Education Study Program at Medan State University, with a focus on identifying language errors in academic communication. This study uses a qualitative descriptive method with data obtained through an open questionnaire administered to 12 students. The analysis was conducted on four categories of language problems, namely syntactic errors, morphological errors, code-mixing, and the use of informal expressions in formal contexts. The results showed that syntactic errors were the most dominant (36%). Other errors included morphology (24%), code-mixing (22%), and the use of informal language in formal situations (18%). The dominance of syntactic errors reflects students' weak ability to construct effective sentences, while the tendency to code-mix is influenced by the use of foreign terms in the field of cosmetology. These findings highlight the importance of strengthening academic literacy, writing training, and adapting foreign terms into Indonesian to support effective academic communication.